Strategies for optimizing intravenous prostacyclin-analog therapy in patients with pulmonary arterial hypertension. Issue 1 (2nd January 2022) - Ewert, Ralf; Habedank, Dirk; Halank, Michael; Stubbe, Beate; Opitz, Christian F.
ABSTRACT: Introduction: Intravenous prostacyclin-analogs (PCA, e.g. epoprostenol, treprostinil, iloprost) have become an essential part in the therapy of patients with pulmonary hypertension (PH), mainly pulmonary arterial hypertension (PAH). They show considerable differences in pharmacology. A combination therapy including intravenous drugs is regarded as the 'gold standard' in most of PAH patients. Areas covered: This review discusses and summarizes the studies and concepts on which this therapy is based. To date, intravenous prostacyclin-analogs are mainly administered when standard therapy fails to improve patients to low-risk status. However, preliminary data from uncontrolled studies suggest that an 'upfront triple' therapy including intravenous or subcutaneous prostacyclin-analogs could be preferable in selected patients. Expert opinion: Various IV PCA have been evaluated in the treatment of patients with PAH. Today, combination therapy is the 'gold standard' for the majority of patients. Intravenous PCA is recommended from functional class III onwards. Timing of its initiation is still a point of discussion. An escalation of therapy to IV or SC PCA is always necessary if a low-risk status cannot be achieved with other targeted therapies. Preliminary data suggest that selected patients could benefit from an 'upfront triple' therapy. Controlled studies on which such recommendation could be based are lacking.